High-performance polybenzimidazole blend membranes based on a commercially available anion-exchange polymer and F6PBI for vanadium redox flow batteries - Stonawski, Julian; Schroeder, Melanie; Gördes, Janett; Hager, Linus; Hutzler, Andreas; Böhm, Thomas; Thiele, Simon; Kerres, Jochen (Journal of Applied Polymer Science, 2024)
Renewable energy is essential for the transition to a carbon-neutral society. Due to their intermittent nature, temporary storage is required. The all-vanadium redox flow battery (VRFB) is a promising technology for this purpose. Commercially available membranes, such as the FAPQ330 from Fumatech BWT, already show reasonable performance but still have room for improvement in selectivity and conductivity. In this study, we developed new ductile porous blend membranes based on the polybenzimidazole F6PBI by mixing it with poly(diallyldimethylammonium bis(trifluoromethane)sulfonimide), which was prepared from the commercially available poly(dimethylammonium chloride) (PDADMAC). Three types of membranes with different amounts of PDADMA*TFSI in the blend solution were prepared and characterized. Ex-situ conductivity measurements showed conductivities between 8.3 and 30.5 mS cm−1. Ex-situ permeability tests revealed significantly lower permeabilities compared to the reference membrane FAPQ330. No change in ex-situ conductivity was measured after the ex-situ stability test. F6PBI-PDAD37 reached the highest energy efficiency at 50, 100, and 200 mA cm−2 among all tested membranes. For example, a VRFB single-cell equipped with F6PBI-PDAD37 showed an improved EE of 76.5% at 200 mA cm−2, which is higher than the EE of FAPQ330 (74.3%).
CRIS-Team Scopus Importer:2024-10-18
Keywords: blend membranes; ion-conducting polymers; poly(diallyldimethylammonium chloride); polybenzimidazole; vanadium redox flow batteries